The effect of high glucose on the inhibitory action of C21, a selective AT2R agonist, of LPS-stimulated tissue factor expression in human mononuclear cells. Issue 1 (December 2016) - Balia, Cristina; Scalise, Valentina; Cianchetti, Silvana; Faita, Francesca; Neri, Tommaso; Carnicelli, Vittoria; Zucchi, Riccardo; Celi, Alessandro; Pedrinelli, Roberto
Abstract Background Intimate links connect tissue factor (TF), the principal initiator of the clotting cascade, to inflammation, a cross-talk amplified by locally generated Angiotensin (AT) II, the effector arm of the Renin Angiotensin System (RAS). C21, a selective AT2R agonist, downregulates the transcriptional expression of TF in LPS-activated peripheral blood mononuclear cell(PBMC)s implying the existence of ATII type 2 receptor (AT2R)s whose stimulation attenuates inflammation-mediated procoagulant responses. High glucose, by activating key signalling pathways and increasing the cellular content of RAS components, augments TF expression and potentiates the inhibitory effect of AT1R antagonists. It is unknown, however, the impact of that stimulus on AT2R-mediated TF inhibition, an information useful to understand more precisely the role of that signal transduction pathway in the inflammation-mediated coagulation process. TF antigen (ELISA), procoagulant activity (PCA, 1-stage clotting assay) and TF-mRNA (real-time polymerase chain reaction) were assessed in PBMCs activated by LPS, a pro-inflammatory and procoagulant stimulus, exposed to either normal (N) or HG concentrations (5.5 and 50 mM respectively). Results HG upregulated TF expression, an effect abolished by BAY 11-7082, a NFκB inhibitor. C21 inhibited LPS-stimulated PCA, TFAg and mRNA to an extent independent of glucose concentration but the response to Olmesartan, an AT1R antagonist, was quite evidently potentiated by HG. Conclusions HG stimulates LPS-induced TF expression through mechanisms completely dependent upon NFkB activation. Both AT2R-stimulation and AT1R-blockade downregulate inflammation-mediated procoagulant response in PBMCs but HG impacts differently on the two different signal transduction pathways.